Ideologi dalam Bahasa Mufasir: Analisis Marji’ al-Ḍamir pada Tafsir al-Kasysyāf Karya az-Zamakhsyari - Nor Lutfi Fais; Musyafiq, Ahmad (Sunan Kalijaga Islamic State University, 2022)
The methodology can be used in the interpretation of the Qur'an is ra’y, means ijtihad. In order to produce a correct methodologically interpretation, ra’y should be accompanied by certain requirements and methodological steps, such as knowing the rules of interpretation and linguistic sciences. Al-Kasysyaf is one of many interpretation books have been criticized by the strong ideological tendencies of its commentator. It can be seen in the interpretation of verses which have ideological content. Since Al-Zamakhsyari, the commentator, was also known by his expertise in language and literature, it raises a question, what if the verses contain ideology are not possible to be interpreted according to i’tizal when follows the rules of linguistic? This question is what the author intends to examine. This study aims to the implementation of the rule of marji‘ al-dlamir in verses mention the word man yasya’. After using both linguistic approach and theological approach to determine the direction of the interpretation produced by Al-Zamakhsyari, the study found that the rule of marji‘ al-dlamir is still applied thoroughly. However, the result of interpretation still has the nuance of i’tizal because of the takwil used by Al-Zamakhsyari.